Psychological Well-Being Influenced by Self-Compassion and Loneliness among Overseas Students in Jakarta - Misykat Malik Ibrahim; Anisia Kumala Masyhadi; Eka Damayanti; Mukjizah Mukhtar Lutfi (Journal of Educational, Health and Community Psychology, 2022)
Â The importance of psychological well-being for overseas students affects positive psychological functions that have a positive impact both internally (on themselves) and externally (on their circles). This research is a quantitative approach which aims at finding out the influence of self-compassion on psychological well-being, with loneliness as a mediator among them. There are 160 overseas students in Jakarta, who were selected based on a purposive sampling technique. The data collection applied a psychological scale. The scale used to measure self-compassion was adapted from the Self Compassion Scale-Short Form, and the scale used to measure psychological well-being was adapted from the Ryff Psychological Well-Being scale. The scale used to measure loneliness is called the R-UCLA Loneliness Scale (Version 3). The data were analyzed using a double regression test. The results showed: a) self-compassion has a negative influence on loneliness by 27% (R2 = 0.2736), b) loneliness has a negative influence on psychological well-being by 30% (R2 = 0.302), c) self-compassion has a positive influence on psychological well-being by 35% (R2 = 0.3587), and d) the influence of loneliness as a mediator of self-compassion toward psychological well-being is 43% (R2 = 0.4358).